Asumsi Dasar Pembentukan Lingkungan Peradilan Agraria Dalam Pendekatan Sistem Hukum - Andjarwati, Any (Jurnal Hukum & Pembangunan, 2023)
The resolution of land and natural resource disputes through litigation encounters a complex set of issues, including protracted and convoluted processes, high costs, overlapping judgments for the same dispute object, and difficulties in executing verdicts. These unresolved issues can be partly attributed to the characteristics of judicial institutions in Indonesia, where constraints within the Constitution on the formulation of judicial authority for the establishment of an agrarian judiciary are a contributing factor. The aforementioned scenario is also associated with the nature of agrarian disputes, encompassing both public and private legal domains, thereby necessitating the resolution of such conflicts through specific mechanisms. Additionally, the incongruity of agrarian legislation and regulations, stemming from the causal nature of substantive legal issues, requires the elucidation of laws through the systematic organization of agrarian law (comprising reconstruction, reinterpretation, and creation) to uphold law, justice, and tangible benefits. This presents a substantial and essential duty for judges, which cannot be supplanted by ad hoc judges or by the existing design of judicial institutions. This circumstance further underscores the imperative need for the establishment of an agrarian judiciary in Indonesia.